2003
DOI: 10.1073/pnas.1734110100
|View full text |Cite
|
Sign up to set email alerts
|

A calmodulin-binding protein fromArabidopsishas an essential role in pollen germination

Abstract: Calmodulin (CaM), a ubiquitous multifunctional calcium sensor in all eukaryotes, mediates calcium action by regulating the activity͞ function of many unrelated proteins. Although calcium and CaM are known to play a crucial role in pollen germination and pollen tube growth, the proteins that mediate their action have not been identified. We isolated three closely related CaM-binding proteins (NPG1, NPGR1, and NPGR2) from Arabidopsis. NPG1 (No Pollen Germination1) is expressed only in pollen, whereas the NPGrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 61 publications
(67 reference statements)
2
75
0
Order By: Relevance
“…CaM is a ubiquitous multifunctional calcium sensor in all eukaryotes that mediates calcium action by regulating the activity/function of many unrelated proteins. Calcium and CaM are known to play a crucial role in pollen germination and pollen tube growth (Golovkin and Reddy, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…CaM is a ubiquitous multifunctional calcium sensor in all eukaryotes that mediates calcium action by regulating the activity/function of many unrelated proteins. Calcium and CaM are known to play a crucial role in pollen germination and pollen tube growth (Golovkin and Reddy, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two different CAMBPs characterized in Arabidopsis, ACA9 (Autoinhibited Ca 2? ATPase) (Schiøtt et al 2004) and NPG1 (No Pollen Germination1) (Golovkin and Reddy 2003), have been reported to be required for pollen germination and pollen tube growth. ACA9 gene is primarily expressed in pollen and mutations in this gene result in a semisterile phenotype, due to the functions played by this plasma membrane Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…5). Consistently up-regulated are general genes with known functions in pollen germination and tube growth, such as Vanguard1 (At2g47040; Jiang et al, 2005) and No Pollen Germination1 (At2g43040; Golovkin and Reddy, 2003;Fig. 5).…”
Section: Microarray Data Validationmentioning
confidence: 92%